Physical exercise in the context of orthodox ontology - Gojković Goran; Ahmetović Zlatko; Nešić Milan (University Educons, Faculty of Sports and Tourism, Novi Sad, 2016)
Christianity has never denied the importance of the body, but unlike the West where the cult of the body and the physical is present, it has always given precedence to the spirit. This is where the essence lies - in the balance between mind and body in the identity of man. Hence, the seemingly redundant analysis when the ontology of the Church is concerned, but it is, simply, the modality in which this is presented in the language of Orthodox ontology. Therefore, as a principle assumption, it can be argued that sport is nothing but a secularized form of Christianity. This is confirmed by many examples, both in the literature of the philosophy of sport (primarily), and likewise in everyday practice. Although these examples, for the most part, are secular in nature, they, nevertheless, demonstrate a high degree of that which is complimentary with the principles of the Christian asceticism. Hence, the asceticism (Orthodox) and sport present the deepest aspirations of the human soul, viz. body, namely: perfection, harmony, beauty, goodness, truth, holiness. With asceticism, a Christian is elevated above the level of animal rationale, and what else does sport do, if not the same. Asceticism exhausts its essence in man's inherent aspiration towards Beauty (God) and beauty (of the soul), while sport represents this identical aspiration through physical feat and skill. This work, through the form of a descriptive study, in its basis, deals with the topic of comparative considerations/display of kinetic phenomena in sport (mainly) and in the experiment (experience) of ascetic practice, as basic guiding threads of Orthodox ontology.